2021
DOI: 10.1002/ptr.7067
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid, kaempferol‐3‐O‐apiofuranosyl‐7‐O‐rhamnopyranosyl, as a potential therapeutic agent for breast cancer with a promoting effect on ovarian function

Abstract: It is widely known that breast cancer cells eventually develop resistance to hormonal drugs and chemotherapies, which often compromise fertility. This study aimed to investigate the effect of the flavonoid, kaempferol-3-O-apiofuranosyl-7-O-rhamnopyranosyl (KARP), on 1) the viability of MCF-7 breast cancer cells and 2) ovarian function in rats.A dose-dependent decrease in MCF-7 cell survival was observed, and the IC50 value was found to be 48 μg/ml. Cells in the control group or those exposed to increasing conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…Through comparison each gene of our gene signature with existing studies separately, we found that there are many studies on the association between gene PTGS2, gene SQSTM1 and breast cancer. Researches on gene LINC01125 [ 25 ], gene GDF9 [ 41 , 42 ] and gene GVINP1 [ 43 ] is very limited, no studies have shown that there is a link between gene TMEM64 and breast cancer. Most of the genes we have proposed in this research have been biologically verified, which also proves the reliability of our gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…Through comparison each gene of our gene signature with existing studies separately, we found that there are many studies on the association between gene PTGS2, gene SQSTM1 and breast cancer. Researches on gene LINC01125 [ 25 ], gene GDF9 [ 41 , 42 ] and gene GVINP1 [ 43 ] is very limited, no studies have shown that there is a link between gene TMEM64 and breast cancer. Most of the genes we have proposed in this research have been biologically verified, which also proves the reliability of our gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…6E) with roles in reproductive biology and signal transduction [74][75][76] [77], emerged as a key CCI with the same directionality across multiple cell types. These genes have been implicated in BC prognosis and therapeutic outcomes [78] [79][80], with BMPR1B exhibiting dual roles in chemotherapy response [81][82][83]. Another top CCI involved the renowned GDNF -RET signaling pathway interactions between 'NRTN' (neurturin), or its paralog 'ARTN' (artemin), and 'GFRA1' (GDNF family receptor alpha 1) in multiple cell types (Fig.…”
Section: Identifying Key Cell-cell Interactions Associated With Chemo...mentioning
confidence: 99%
“…Furthermore, KV triggers the overproduction of ROS by upregulating LC3-II and p62, leading to autophagy-mediated cell death. Harrath et al (2021) discovered that kaempferol-3-O-apiofuranosyl-7-O-rhamnopyranosyl can enhance ROS production, inducing dose-dependent autophagy and apoptosis of MCF-7 breast cancer cells. The findings suggest that the compound may be a promising treatment for breast cancer patients ( Figure 4 ).…”
Section: Mechanisms Of Kaempferol Against Gynaecological Malignanciesmentioning
confidence: 99%